ESTUDO DA APLICAÇÃO DE ANTIOXIDANTE NATURAL PARA BIODIESEL E ÓLEO DE SOJA - Boschen, Nayara Lais (2016)
The use of biodiesel to replace petroleum diesel, significantly increased the studies related this biofuel, and in production, quality, alternative routes and adding different antioxidants to prevent lipid oxidation of oils. These compounds may be synthetic or natural, both are widely used. However synthetics can cause damage to the human body unlike natural. Tocopherol (vitamin E) is an example of a widely used due to its antioxidant effectiveness. The agroindustrial waste macerated barley contains in its composition tocopherol, featuring its high antioxidant activity. The objective of this paper is to use the residue of macerated barley as natural antioxidant applied to soybean oil and biodiesel. As techniques were used near infrared spectroscopy, Raman spectroscopy, elemental composition analysis, accelerated oxidation test (873 Rancimat®) micro distillation system in infrared analysis density, conductivity, pH, viscosity, water content (Karl Fischer) and the experimental design was 3². For treatment and use of the residue is necessary several stages in different ways: neutral, acidic or basic. These steps resulted in three biodiesel production processes with the addition of natural antioxidant, without considering the variable concentration of antioxidant. Results for soybean oil in a concentration of 10 g L-1 and residue concentration of 5.0% (v / v) solvent extraction (hydrochloric acid) led to an induction time of (13.95±0.05) h. When compared with the results obtained for the commercial refined soybean oil without addition of agroindustrial residue, which was (7.16±0.01) h, observed that the increase in antioxidant activity was approximately 47%. The induction time results for biodiesel by adding citric acid was 0.1% 5.5h, adding to the residue (11 g L-1) was 5.8 h for the combination of the two antioxidants (residue + citric acid) was obtained 16,20h. These results are higher than required by the resolution of the ANP, 8h.